Analysis of 22Na using a spectral summation technique on high-volume aerosol samples. (April 2017) - Hoffman, I.; Lewis, B.; Chan, P.; Ungar, K.
Abstract: Measurement of cosmogenic 22 Na in daily aerosol samples is often difficult due to low atmospheric production rates. A new technique based upon spectral summation of sequential high-volume aerosol samples to measure 22 Na is described and validated. This summation technique has broad applications to any detection system that produces sequential representative sample measurements in which radioisotopes are just below the detection limit, provided the energy calibration is stable. It is anticipated that a global dataset of this radionuclide will have many important environmental science applications. Highlights: A spectral summation technique was developed and applied to detect previously unquantifiable 22 Na in aerosol samples. This technique requires a stable energy calibration of the detection system and works with any integration period. This technique has broad applicability to any spectroscopic analysis of radionuclides near or below the limit of detection.